The concept of Buen Vivir in the context of green theory in international relations - A. A. Shinkarenko; V. X. Medina González; B. I. Nekrasov (Ибероамериканские тетради)
The authors consider the peculiarities of emergence of Buen Vivir сoncept in the context of increasing importance of the environmental factor in international relations. The authors present the main ideas of this concept, which became a logical response to environmental challenges – first from the autonomous societies of Latin America, and then found its reflection at the state level in countries such as Ecuador and Bolivia. At the same time, for the first time in Russian historiography, we present an analysis of this concept connection to the development of such a direction in international relations as environmentalism, as well as what place it can occupy in the international relations theory. The main results of the research are as follows: 1) the role and significance of the environmental factor in modern IR is increasing, while politicization of environmental problems is observed; 2) the number of studies on topics related to environmentalism in IR is increasing, with them becoming one of the dominants of not only public, but also a research discourse; 3) the concept of sustainable development did not fully comply with existing demands, which predetermined the emergence in Latin America of a separate concept of development, with an emphasis on the environmental component, being a Latin American ‘response’ to the search of a model for regulating the relationship of mankind with the environment in order to preserve it; 4) the concept of Buen Vivir was most successfully implemented in Ecuador and Bolivia as these countries are home to a significant number of Native Indians, and their worldview is closely intertwined with the key ideas of the concept.